Pengaruh Kualitas Produk, Persepsi Harga Dan Promosi Terhadap Keputusan Pembelian Di Kopi Kenangan Ruko Muara Karang - Mochammad Aditya Safar; Bonifasius MH Nainggolan (Human Capital Development, 2023)
This study aims to determine the effect of product quality (X1), price perception (X2), and promotion (X3) on purchasing decisions (Y) partially and together on Kopi Kenangan Ruko Muara Karang. The sampling technique used in this study was purposive sampling using SmartPLS 3.0 and processing the data using PLS-SEM Path Analysis. The sample used was the consumers of Kopi Kenangan, Ruko Muara Karang, as many as 220 respondents. The results of the analysis obtained from this study are that the perception of price and promotion has a significant effect on purchasing decisions, while there is no significant effect on product quality variables on purchasing decisions.